Enhanced anti-microbial corrosion of nano-CuO-loaded Ni coatings on pipeline steels in simulation environment of natural gas transportation pipeline. Issue 3 (1st February 2023) - Zhu, Lixia; Tang, Yufei; Cao, Siyue; Jiang, Junyi; Wu, Cong; Zhao, Kang
Abstract: Bacteria were introduced into natural gas transportation lines and reacted with CO2 and corrosive ions to cause severe corrosion when natural gas was captured by water drive methods. Anti-microbial corrosion of natural gas pipeline is an important prerequisite for pipeline steel protection. An Ni coating with high corrosion resistance was prepared on the surface of pipeline steel by electrodeposition method, and CuO nanoparticles were introduced to obtain anti-microbial function. A simulated corrosion environment in a natural gas pipeline was designed to investigate the corrosion resistance behavior of the CuO-loaded Ni coating under the combined action of CO2, Cl −, and sulfate-reducing bacteria (SRB) and the inhibition effect of CuO on the microbial corrosion of SRB. The corrosion rate of nano-CuO-loaded Ni coatings at 15 days was only 41.8% of that of the pipeline steel. In addition to the corrosion resistance of the Ni coating, the corrosion rate was reduced because nano-CuO reduces the probability of corrosion reactions and has an anti-microbial effect on SRB. This coating with anti-microbial and anticorrosive functions has important engineering application value for the microbial corrosion protection of natural gas pipelines.